The Influence of Brand Equity and Word Of Mouth on Purchase Decisions (Case Study at Umama Gallery Karawang) - Thifal Mutiarani; Banuara Nadeak; Solehudin (Institute of Computer Science (IOCS), 2022)
Equity and Word of Mouth are some of the factors in retail companies that can be used as a reference for consumers to make purchasing decisions on a product brand. Ifna company wants to strengthen its brand among the people, then the company must have a good marketing strategy so that its brand is always remembered by consumers even though many similar products are circulating in the market. This study aims to determine how much influence Brand Equity and Word of Mouth have on Purchasing Decisions on Umama brand products. The method used is descriptive and verification with quantitative approaches. Data were analyzed using path analysis and hypothesis estingv using t test and fntest. The results showed that BrandnEquity had a partially positive effect as evidenced by the tcount of 18,412 with a significant value of 0,000, which means positive, Word of Mouth also had a partially positive effect as evidenced by a tcount ofn5,174 with a ignification value ofn0,000, which means positive, andnBrand Equity and Word ofnMouth which simultaneously have apositive effect on purchasing decisions as evidenced by a calculation of 53,753 with a significance value ofn0,000 which means that purchasing decisions can be influenced by Brand Equity and WordnofnMouth by 77.4% and the rest is influenced by other variables of 66.9% which is not contained in this study.